2010
DOI: 10.1111/j.1708-8208.2009.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Bone Healing around Different Implant Bulk Designs and Surgical Techniques: A Study in Dogs

Abstract: Different implant design/surgical protocol resulted in varied bone healing patterns. However, the BIC and bone morphology evolution between implant designs were comparable. Regardless of the combination between implant design and final osteotomy drilling, bone morphology evolution from 2 to 4 weeks was comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 19 publications
8
85
0
5
Order By: Relevance
“…While a plethora of studies concerns the effects of micrometer and more recently nanometer scale design parameter contribution to osseointegration, a significantly smaller body of work is available regarding how hardware design aspects affect osseointegration. For instance, far less explored in the literature is how osseointegration temporally occurs around endosteal implants substantially shift as a function of two major key implant design parameters: implant macrogeometry and its associated surgical instrumentation [22][23][24]. While it is obvious that two different design parameters are under consideration, their contribution to the healing mode cannot be considered separately [22,23].…”
Section: The Effect Of Implant Macrogeometric (Hardware Design) In Bomentioning
confidence: 97%
See 2 more Smart Citations
“…While a plethora of studies concerns the effects of micrometer and more recently nanometer scale design parameter contribution to osseointegration, a significantly smaller body of work is available regarding how hardware design aspects affect osseointegration. For instance, far less explored in the literature is how osseointegration temporally occurs around endosteal implants substantially shift as a function of two major key implant design parameters: implant macrogeometry and its associated surgical instrumentation [22][23][24]. While it is obvious that two different design parameters are under consideration, their contribution to the healing mode cannot be considered separately [22,23].…”
Section: The Effect Of Implant Macrogeometric (Hardware Design) In Bomentioning
confidence: 97%
“…Such healing chambers, filled with the blood clot, will evolve toward osteogenic tissue that subsequently ossifies through an intramembranous-like pathway [42]. Noteworthy is that unlike the interfacial remodeling healing pathway, healing chamber configurations do not encompass the initial cleanup process due to microcracking and ostecompression [22,42,44]. In this case, the blood filling the space between pristine bone and device will develop toward a connective tissue network that provides a seamless pathway for cell migration within the space once filled by the blood clot (Fig.…”
Section: 2mentioning
confidence: 98%
See 1 more Smart Citation
“…Since interfacial bone modeling and remodeling (and potentially bone kinetics and mechanical properties) has been shown to change as a function of the interplay between surgical instrumentation and implant geometry (Coelho et al, 2010), the region between threads was subdivided into four bone quadrants as depicted in Figure 1C. Bone tissue was detected by imaging under the light microscope (Hysitron TI 950, Minneapolis, MN, USA) (Butz et al, 2006) and indentations were performed in the selected areas.…”
Section: Nanoindentationmentioning
confidence: 99%
“…Extensive surface characterization has shown that RBM-treated surfaces are less rough than titanium surfaces blasted with alumina particles and possess a nonhomogenous distribution of CaP, depending on several factors, such as the composition of the basting media, the particle size and other processing parameters 21 .…”
Section: Introductionmentioning
confidence: 99%